Divergent Soybean Calmodulins Respond Similarly to Calcium Transients: Insight into Differential Target Regulation - Walton, Shane D.; Chakravarthy, Harshini; Shettigar, Vikram; O’Neil, Andrew J.; Siddiqui, Jalal K.; Jones, Benjamin R.; Tikunova, Svetlana B.; Davis, Jonathan P. (Frontiers in Plant Science, 2017)
Plants commonly respond to stressors by modulating the expression of a large family of calcium binding proteins including isoforms of the ubiquitous signaling protein calmodulin (CaM). The various plant CaM isoforms are thought to differentially regulate the activity of specific target proteins to modulate cellular stress responses. The mechanism(s) behind differential target activation by the plant CaMs is unknown. In this study, we used steady-state and stopped-flow fluorescence spectroscopy to investigate the strategy by which two soybean CaMs (sCaM1 and sCaM4) have evolved to differentially regulate NAD kinase (NADK), which is activated by sCaM1 but inhibited by sCaM4. Although the isolated proteins have different cation binding properties, in the presence of Mg²⁺ and the CaM binding domains from proteins that are differentially regulated, the two plant CaMs respond nearly identically to rapid and slow Ca²⁺ transients. Our data suggest that the plant CaMs have evolved to bind certain targets with comparable affinities, respond similarly to a particular Ca²⁺ signature, but achieve different structural states, only one of which can activate the enzyme. Understanding the basis for differential enzyme regulation by the plant CaMs is the first step to engineering a vertebrate CaM that will selectively alter the CaM signaling network.